Chemisorptive enantioselectivity of chiral epoxides on tartaric-acid modified Pd(111): three-point bonding. Issue 7 (21st February 2015) - Mahapatra, Mausumi; Tysoe, Wilfred T.
<x xml:space="preserve">Abstract</x> The chemisorption of two chiral molecules, propylene oxide and glycidol, is studied on tartaric-acid modified Pd(111) surfaces by using temperature-programmed desorption to measure adsorbate coverage.